The Influence of Pop-Up Book Media on The Learning Outcomes of Class IV Students on The Subject of Social Sciences, Theme 1, Subtema 3 at SDN 0949109 Raya Pinantar - Irene Maudy Tamara Haloho; Lisbet Sihombing; Selamat Triadil Saragih (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of pop-up book media on the learning outcomes of class IV students in social studies subjects theme 1 subtheme 3 at SD Negeri 094109 Raya Pinantar. This research is a type of quantitative research using experimental methods with a one group pretest-posttest design type of research . The population of this research is all fourth grade students at SD 094109 Raya Pinantar FY 2023/2024, totaling 25 students. The research results at the 0.05 level show that there is an influence of Pop-Up Book media on student learning outcomes. After carrying out the validity of the test, a pretest was carried out with an average score of 52.48 and the posttest results showed that the average score for class IV students was 83.20. By using the N-Gain Test, an average value of 63.27 is obtained, so the results of the N-Gain test are in the medium category, judging from the provisions of the assessment criteria, if 0.70 < n- gain , then the assessment criteria are high, and if 0, 30 < n-gain < 0.70 then the assessment criteria are medium, and if n-gain < 0.30 then the assessment criteria are low. Thus it can be concluded that there is a significant difference between increasing learning outcomes using Pop-Up Book media and increasing learning outcomes without using Pop-Up Book media.